The Petroleum Manga: A Project by Marina Zurkow - Zurkow, Marina; Project Muse; Project Muse. (Project Muse, 2020)
The Petroleum Manga, first conceived of and rendered as 10-foot banners printed on Tyvek for gallery installation is now reproduced in book form. Originally, manga was used in Japanese to refer to whimsical drawings or picture books. Long before Manga was a multi-billion-dollar-a-year comic book industry, there was Hokusai's thirteen-volume manga, depicting everything from trees to demons, from squirrels to shingles. This was the work that inspired the form for Marina Zurkow's own crazy amalgam depicting a taxonomy of products derived from petroleum. Remaining true to this inspiration, this book compiles a curious array of imaginative-philosophical texts illuminating, illustrating, fabulating, and riffing upon a wide range of petrochemical-based objects and ideas. This "collection" maps new webs of relations between us and these seemingly ubiquitous yet often unremarked objects, along the lines of a fanciful petro-poetics. Fanciful, yet dead serious. As Duncan Murrell writes, "...our plastics will live forever, no longer able to decompose, while we become molecules again. When we are long gone, there will still be plastic clown masks circling in the Pacific Ocean. This, and not our great works of art and literature, will be the persistent legacy of life on earth, these objects crafted out of life's own ancient flesh."
Issued as part of book collections on Project MUSE.
2015 Poets House Showcase.
Description based on print version record.
Keywords: Comic books, strips, etc. -- Influence; Prose poems, American -- 21st century; Short stories, American -- 21st century; Arts, American -- 21st century; Petroleum chemicals -- In literature; Electronic books; Electronic books